Black Suns of Melancholy Hart Crane’s Treatment of the Sun Motif in the Light of Mircea Eliade’s Study of Solar Cults - Alicja Piechucka (European Journal of American Studies)
The aim of the article is to examine Hart Crane’s use of solar imagery in the light of Mircea Eliade’s study of solar cults. The Crane poem under consideration is his elegy for Harry Crosby, a publisher, fellow poet and friend, who was a sun devotee and one of the most flamboyant figures on the 1920s American literary scene. The work by Eliade on which the article draws is his seminal book Patterns in Comparative Religion. Filtered through the insights provided by the Romanian-born scholar, Crane’s elegy, all too often dismissed as a minor poem, takes on new meanings. In the light of Eliade’s illuminating analysis of solar symbolism and the role the sun plays in different cultures, the poem emerges as a carefully constructed reflection on the artist’s fate. The article demonstrates that Crane’s use of seemingly familiar solar imagery may in fact serve to highlight the need for inspiration, the pursuit of perfection and completeness or the yearning for artistic immortality - issues inscribed into a neo romantic view of the artist’s condition.